Exploration on the Construction and Enhancement Strategies of Vocational Competitiveness of Higher Vocational Students from the Perspective of Vocational Skills Competitions - Li Weishuo (Journal of Exploration of Vocational Education, 2025)
Abstract: This study explores the construction and transformation mechanism of vocational competitiveness of higher vocational students from the perspective of vocational skills competitions. The research finds that skills competitions significantly enhance students’ vocational competitiveness by improving their professional skills, innovation ability, team collaboration, and professional literacy. The research results provide important reference value for optimizing the curriculum settings of higher vocational education and promoting school-enterprise cooperation.